Quaternary Phosphonium Carboxylates: Structure, Dynamics and Intriguing Olefination Mechanism - Vetter, Anna C.; Müller-Bunz, Helge; Muldoon, Jimmy; Nikitin, Kirill (Synthesis, 2021)
We have earlier shown how the Wittig chemistry can be done using novel Eigenbase phosphonium carboxylate reagents. Here we discuss the phenomenon of ion pairing, their solution tautomerism, solid-state structure, and mechanistic aspects of olefination. The results point to a complex process involving unfamiliar H-bond-driven ion-pair equilibria followed by standard Wittig reaction steps.
Keywords: quaternary phosphonium salts; ion pairs; Wittig reaction; proton-transfer equilibrium; fluxional behaviour